Survey Hasil Pelaksanaan Katekese Umat Tentang Literasi Ekologis Bagi Penyandang Disabilitas Di Wisma Bhakti Luhur Mondoroko Malang - Sri Wahyuni; Yovita Kui (Jurnal Pelayanan Pastoral, 2021)
Providing an understanding of ecological literacy should not only be given to the general public (normal) but must also be given to persons with disabilities The purpose of this study was to obtain an overview of the implementation of catechesis by people regarding ecological literacy for persons with disabilities in the saint Filemon Mondoroko Malang. The research subjects were persons with disabilities residing in the Mondoroko hostel in the area of ​​Saint Filemon. The data collection technique was using a questionnaire. The instrument used for this questionnaire method was a Gutman scale questionnaire with a firm answer, yes or no. The sample used is random sample sampling. This type of research is quantitative research. The research design is survey research. The total population is 42 persons with disabilities in the Bhakti Luhur Mondoroko guesthouse, while the sample is 10 persons with mental retardation disabilities. From the results of the real action survey research on the implementation of catechesis of the people on ecological literacy for people with mental retardation, the results were quite significant, namely that out of 10 people with mental retardation who were monitored, the results were 93.9%. This shows that they are very enthusiastic about taking part in environmental care. But it should also be remembered that because they are persons with disabilities, their real actions need to be continuously monitored.